The “Incubators” as Research Spaces for the Novice Researcher - Nahín Numa-Sanjuan; Rodolfo Alfonso Márquez Delgado (Propósitos y Representaciones, 2019)
This article of empirical and interpretive nature aims to offer a contribution to the discussion of “Incubators” as research spaces in the formation of the novice researcher. It is a product of reflections carried out by the authors on the subject and discussions carried out with undergraduate and graduate young people who aspire to be researchers in the field of education. It is based on a reference framework related to: a) research as a systematic process that is learned and taught and; b) competences in research for the training of novice researchers. It is based on the assumption that to do a research in the field of Education Sciences is complex. However, this makes them fertile and an incubator for research competences. It is concluded with the proposal of three actions or paths associated with the training of novice researchers: to) the institutionalization of “Incubators” as research spaces; (b) the production of scientific papers and; (c) the implementation of the curriculum research. The expectation of the authors is that these reflections contribute to promote educational institutions spaces such as the research “Incubators” allowing them to exceed the research gaps that currently exist in Latin America and that they consolidated as organizations that learn and manage knowledge.